1993
DOI: 10.1017/s0266467400007045
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal and vegetation dynamics at a cock-of-the-rock's lek in the tropical forest of French Guiana

Abstract: THfiRY, M. 1990. Ecologie et comportement des oiseaux Pipridae en Guyane: leks, frugivorie et dissemination des graines. These de Doctoral de PUniversite Paris 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 4 publications
0
23
1
Order By: Relevance
“…Contrary to our expectations, the seed abundance and species richness in the seed rain was similar between lek and non-lek areas, paralleling what Krijger et al (1997) found for M. manacus in French Guiana, but in sharp contrast to other lekking bird species (Karubian et al 2012, Théry & Larpin 1993. The reasons for the differences between M. manacus and the few other lekking species studied so far regarding seed rain in lek areas remain elusive.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Contrary to our expectations, the seed abundance and species richness in the seed rain was similar between lek and non-lek areas, paralleling what Krijger et al (1997) found for M. manacus in French Guiana, but in sharp contrast to other lekking bird species (Karubian et al 2012, Théry & Larpin 1993. The reasons for the differences between M. manacus and the few other lekking species studied so far regarding seed rain in lek areas remain elusive.…”
Section: Discussioncontrasting
confidence: 64%
“…While males remain stationary in lek areas where they hold display territories, females and juveniles generally move widely to visit different leks (Graves et al 1983, Théry 1992. The long permanence of males in lek areas often result in the deposition of a great variety and density of seeds that ultimately may influence the structure and composition of the vegetation (Karubian et al 2012, Krijger et al 1997, Théry & Larpin 1993.…”
Section: Introductionmentioning
confidence: 99%
“…1990, Thiollay 1994. In addition, several other frugivorous birds have lek mating systems in which aggregation of dispersed seeds can be expected (Thery & Larpin 1993). This study justifies further research to the extent in which social behaviour of dispersal agents explains variation in regeneration potential on forest level.…”
mentioning
confidence: 56%
“…Indeed, some of these sites may be used repeatedly for multiple years, inducing clumping over yet longer timescales. J. M. Fragoso (personal communication) has observed some tapir latrine sites used consistently for 12 years, and Théry and Larpin (1993) suggest that the same leks may be used by bird species for multiple generations. Unfortunately, few studies are long enough to document such patterns.…”
Section: Patternsmentioning
confidence: 99%